Inverse association of obesity with bout periodicity in episodic cluster headache: a multicenter cross-sectional study - Byung-Su Kim; Mi Ji Lee; Byung-Kun Kim; Jong-Hee Sohn; Tae-Jin Song; Min Kyung Chu; Soo-Kyoung Kim; Jeong Wook Park; Heui-Soo Moon; Pil-Wook Chung; Soo-Jin Cho (The Journal of Headache and Pain)
Abstract Background Cluster headache (CH) is the most painful headache disorder. Despite a large body of evidence on obesity’s negative influence on migraine, its impact on cluster headache disease activity remains unexplored. We aimed to determine whether body mass index (BMI) and obesity are associated with lifetime bout occurrence and annual bout frequency in patients with episodic cluster headache (ECH). Methods The Korean Cluster Headache Registry (KCHR) is a prospective, multicenter registry of consecutive patients with CH over 4 years. This cross-sectional study included 316 eligible patients with ECH, with ≥ 2 years of duration of CH disease and ≥ 2 times of lifetime bout occurrence. Obesity was determined using the Asia-Pacific classification (obese: BMI ≥ 25.0 kg/m2). Bout frequency was defined as an average annual number of bout occurrence: number of lifetime bout occurrence divided by total duration of CH disease. The main outcomes included odds ratios (ORs) of BMI and obesity for quartiles of lifetime bout occurrence and annual bout frequency by performing ordinal logistic regression analysis. Results The mean (SD) age of the patients was 37 (9.7); 50 (15.8%) were female. The mean (SD) BMI was 23.9 (3.2) kg/m2; 105 (33.2%) were obese. The median (interquartile range) duration of CH disease was 10 (6–16) years; lifetime bout occurrence was 7 (4–12); and annual bout frequency was 0.88 (0.5–1.10). In multivariable adjusted models, OR of BMI (per 1 kg/m2) and the obese group for lifetime bout occurrence were 0.89; 95% CI, 0.84–0.95 and 0.40; 95% CI, 0.23–0.68. Age, BMI, and seasonal propensity were associated factors for annual bout frequency. After multivariable adjustment, BMI and obesity were inversely associated with annual bout frequency (BMI per 1 kg/m2 OR: 0.92; 95% CI: 0.86–0.98 and obese OR: 0.52; 95% CI: 0.32–0.86). Conclusions BMI and obesity were inversely associated with lifetime bout occurrence and annual bout frequency in ECH, suggesting that neurobiological aspects of obesity may suppress cluster bout periodicity. Graphical Abstract